Assessment of the establishment success of surfgrass Phyllospadix iwatensis from shoots in a leaf trimming method: implications for large-scale restoration - Sun, Jie; Luo, Fan-Shu; Yu, Guo-Xu; Zhang, Hong-Yu; Li, Wen-Tao; Zhang, Pei-Dong (Frontiers in Marine Science, 2023)
Phyllospadix spp. play a crucial role in the supply of ecosystem services in rocky shores, but they have been rapidly reduced because of natural and anthropogenic causes. Since Phyllospadix spp. are attached to rocks in the surf zone with a strong hydrodynamic condition, their transplanted shoots easily disappear due to the high current velocity, resulting in the failure of transplantation. We described a leaf trimming method for transplanting shoots of surfgrass Phyllospadix iwatensis and evaluated the method’s establishment success for potential use in large-scale restoration projects. A 30-day laboratory experiment was conducted to determine the effect of leaf trimming on shoot survival, growth, and physiology. Successful establishment of new patches from shoots transplanted with the leaf trimming method was assessed through a shoot-transplanting field experiment over 15 months. The survival of P. iwatensis shoots was not significantly affected by the leaf trimming proportion of 10%–60%. The leaf elongation rate and total leaf area of the shoots exposed to 10%–50% leaf trimming reached or exceeded those of the control at the end of the laboratory experiment; however, the growth of the shoots under 60% leaf trimming was significantly lower than those under the control (p < 0.05). The soluble sugar and starch contents of the shoots also displayed a similar trend to the growth, with the lowest values attained at 60% of leaf trimming. The survival rate of shoots exposed to 50% leaf trimming treatment was 70% after 15 months following transplantation, which was 1.23 times higher than that of shoots in the control (p < 0.05). The shoot height in the 50% leaf trimming treatment was 1.02 times higher than that of shoots in the control at the end of the field experiment. There were no significant differences in photosynthetic pigment contents of P. iwatensis shoots between the leaf trimming treatment and the control (p > 0.05). Our study suggested that the leaf trimming method is an efficient restoration technique for the transplantation of P. iwatensis shoots, and is potentially useful in facilitating large-scale restoration projects.